Boyhood to manhood in one pregnancy : adolescent fathers, a discourse analytical study : a thesis presented in partial fulfillment of the requirements for the degree of Master of Science in Psychology at Massey University - Rouch, Gareth (Massey University, 2003)
This study explores the experience of adolescent fatherhood using the techniques of discourse analysis as developed by Potter and Wetherell (1987). Twelve adolescent fathers were interviewed (ages 16 to 20 years). All had become fathers before turning 19 years of age. They were recruited from either the local community or were referred to the researcher by guidance counselors at select secondary schools. Participation was voluntary and anonymous. Six major discourses were used to construct the experience of adolescent fatherhood. These were: (a)The responsibility discourse. All said they had made major personal and social adjustments to ensure the welfare of their child: (b)The compromised discourse. This positioned their role as a father compromised by societal disinterest and disdain: (c)The agent for change discourse. Fatherhood disposed them to discard self-injurious habits and to cease asocial behavior: (d)Duel identities discourse. Parenthood during adolescence acted to bifurcate their identity: (e)The premature discourse. Accelerated entry into adult roles attenuated their performance as a father: (f)The improvement discourse. Many spoke of wishing to raise their offspring without the detractions which featured in their own childhood. Fatherhood gave many a powerful sense of purpose. Except for those who were prohibited access to their children, all stated the role of being a father was their primary identity and it had an overall beneficial effect upon their lives.
Keywords: Teenage fathers; Adolescent fatherhood; Adolescent fathers